Workplace aggression, wellbeing, and job satisfaction: The specificity in border police organizations - Antón, Concha; Grueso-Hinestroza, Merlin Patricia; Espinosa, Juan C.; Turc, Mirela (Frontiers in Psychology, 2022)
In male-dominated work contexts, the challenges faced by women and their impact on wellbeing and work attitudes have been documented, most extensively in other than police organizations. This study was conducted as a cross-sectional quantitative descriptive correlational predictive study to validate a model of relationships among workplace aggression, job satisfaction, and wellbeing at work with a sample of 1,066 female and male officers from the Romanian Border Police. The results obtained in the study showed that no differential gender effects were found, although women reported higher levels of workplace aggression than men (1.61 vs. 1.52; F = 4.20, p = 0.04). Also, workplace aggression significantly and negatively predicted job satisfaction (R2 = 0.27) and wellbeing at work (R2 = 0.31). In conclusion, although this research is an exploratory approach to the study of workplace aggression in the Romanian police organization, it can generate interventions that would lead to the reduction of undesirable behaviors such as verbal aggression, malicious jokes, discrimination, perception of inequalities, gossip, and defamatory words. In the future lines of research, different sources and conditions of victims and witnesses can be considered the. We also studied the limitations of the study and the future lines of research.